The Implementation of Household Accounting in Families Owning Micro Scale Businesses - Raharjo, Arief Prima; Kamayanti, Ari (Jurnal Ilmiah Mahasiswa FEB, 2014)
Household accounting is not a new discipline there are a lot of researchabout household accounting outside Indonesia. Although a lot of research abouthousehold accounting outside Indonesia but in Indonesia only little research abouthousehold accounting are published, particularly household accountingimplementation in conjugal and extended family owning micro scale businesses.This research purpose is to explain how the implementation of householdaccounting in conjugal family and extended family owning micro scale businessesusing interpretive paradigm. The results of this research are in conjugal familyowning micro scale business they implement household accounting but there is adifferent about accounting in the business. In extended family owning micro scalebusiness household accounting is implemented in the family but it is contrary withthe business. Another interesting finding is wives are trusted by husbands fordisposable and small nominal goods like household appliances, and vegetables butfor goods with big nominal and have long term economic age like refrigerator,motorcycle, and car, husbands involve in decision making. Values exist inhousehold accounting practice are: trust, not redundant (mubazir), religious,preventive, halal, visionary, effective, and efficient.Keywords: Household Accounting, Family Accounting, Conjugal Family,Extended Family, Micro Scale Business, Interpretive